Optical properties of surfaces - Bedeaux, Dick, 1941- (Imperial College Press, 2004)
Annotation - An extremely rigorous theoretical description- For thin films computer programs are available for obtaining the optical properties exactly- Presents optical properties of rough surfaces, including capillary waves and oxide layers- Provides a new discussion on reflection from a gyrotropic surface- Describes reflection from a self-affine rough surface.
Keywords: Surfaces -- Optical properties.; Thin films.; elektronické knihy; electronic books